2009
DOI: 10.1634/theoncologist.2009-s1-57
|View full text |Cite
|
Sign up to set email alerts
|

Is Nephrology More at Ease Than Oncology with Erythropoiesis-Stimulating Agents? Treatment Guidelines and an Update on Benefits and Risks

Abstract: Erythropoiesis-stimulating agents (ESAs), which promote RBC production, have been extensively used to reduce transfusion requirements and improve quality of life (QoL) in both cancer patients and those with chronic kidney disease (CKD). However, the likelihood of response and duration of treatment differ in the two settings. In renal anemia, ESAs act straightforwardly as hormone-replacement therapy. The anemia of cancer, however, relates not to a lack of endogenous erythropoietin production but to diverse aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In our cohort, the mean hemoglobin was 10.3 g/dL during the initiation of ESA therapy. The use of ESA has been under great scrutiny and a moving target [24-27]. There is now a need to reevaluate the management of anemia in CKD and the data from this study will be timely.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, the mean hemoglobin was 10.3 g/dL during the initiation of ESA therapy. The use of ESA has been under great scrutiny and a moving target [24-27]. There is now a need to reevaluate the management of anemia in CKD and the data from this study will be timely.…”
Section: Discussionmentioning
confidence: 99%
“…ESAs were originally studied in chronic kidney disease, with the first publications examining their use in a nephrology setting appearing in 1986. 3,4 ESAs first came to market with the introduction of epoetin alfa in 1989, which was initially approved by the FDA for the treatment of anemia in patients with end-stage renal disease undergoing dialysis. The agent was marketed as Epogen by Amgen for the dialysis market and as Procrit by OrthoBiotech for other markets, including cancer and HIV/AIDS.…”
Section: S-40mentioning
confidence: 99%
“…For patients with cancer-and chemotherapy-related anemia, data indicated that use of ESAs lowered dependence on transfusions, improved QoL, and reduced symptoms of fatigue. 3,6 In 2001, darbepoetin alfa, marketed by Amgen as Aranesp, came to market after a September approval by the FDA for the treatment of anemia associated with chronic renal failure. Darbepoetin alfa had already been approved in June 2001 by the European Medicines Agency (EMEA) for the chronic renal failure indication and the treatment of chemotherapy-induced anemia.…”
Section: Esas: Clinical and Operational Impactmentioning
confidence: 99%